Menu development for portable Qibla finder using GPS: article - Kamarudin, Nurulhuda (2011)
Normally, people use a compass to determine the Qib;s direction but in today developing era, there are so many thinkable solutions such as to design a portable Qibla finder using GPS. The scope of this project is to develop menu using assembly language to be appended into the PIC 16F877A microcontroller that acts as the brain of the whole systems which consists of 5 modules, controller unit module (PIC16F877A to store command), GLCD module (displaying text and gra.phics) and also the input module (tack switch for the navigation puIposes). MPLAB IDE and PROTEUS VSM is used for assembling aad debugging purposes.